Randomized Clinical Study on the Efficacy of Direct Anterior Approach Combined With Tendon Release and Repair After Total Hip Arthroplasty - Li, Guanbao; Chen, Qiuan; Zhou, Wei; Li, Pinquan; Ma, Peng; Liu, Tongyuan; Tang, Hai (Frontiers in Surgery, 2022)
Background: To study the effect of reconstruction of the joint capsule and conjoint tendon on the functional recovery of the hip joint during direct anterior approach (DAA) total hip arthroplasty. Methods: A total of 60 patients who underwent their first total hip arthroplasty surgery were selected. According to the set criteria, the selected patients were divided into observation group A (n=30) and control group B (n=30). In group A, the joint capsule and conjoint tendon (superior muscle, internal obturator muscle, and inferior muscle) were repaired in-situ, while in group B, only the joint capsule was repaired in-situ and conjoint tendon was not repaired. The surgical indicators, including hip joint function and clinical efficacy of the two groups, were compared. Results: After six months of follow-up in groups A and B, no dislocation occurred. The Harris Hip scores of group A were higher than those of group B at 1-month post-operation, i.e., p< 0.05, as well as the valid muscle strength and conjoint tendon valid tension, is higher in group A than group B at one-month postoperative follow-up, i.e., p<0.05. Conclusion: DAA for total hip arthroplasty on the premise of reconstructing the joint capsule structure can rebuild the tension of the conjoint tendon, enhance its muscle strength, and significantly improve the joint stability and function of the patient early stage. It is beneficial for the patient's rapid recovery and is worth implementing.